Purana Amulya Grantha, Tadpatra ra Kalatmak Bastuharu Samrakshyan Garne Adesh Dieako Auta Aaitihasik Kagaj - Sharma kandel, Devi Prasad (Tribhuvan University Journal, 2010)
Not available. Key words: Amulya Grantha; Kalatmak bastu; Adesh Tribhuvan University Journal Vol. XIX, No. 2, 1996 Page: 157-159 Uploaded Date: Nov.1, 2010